Establishment, Powers and Functions of Supreme Court of Pakistan - Hassan, Abida; Khan, Muhammad Mumtaz Ali; Alam, Imran (Annals of Human and Social Sciences, 2023)
The important function that Pakistan’s Supreme Court plays in the nation’s legal and judicial system has been examined in this research. It explores the background of the Supreme Court’s founding and outlines the roles and authority that are incorporated in the Constitution. The Court’s jurisdiction over matters of public concern, its ability to interpret and uphold the law, and its relevance in protecting constitutional rights are all covered in this article. This article has also focus on significant cases and important rulings that have influenced Pakistan’s legal system. The main purpose of this article was to give an overview of the Supreme Court’s development and its function in upholding justice and the rule of law in Pakistan.